A new model for prediction of drop size distribution in a liquid–liquid extraction column. Issue 86 (31st August 2016) - Asadollahzadeh, Mehdi; Torab-Mostaedi, Meisam; Torkaman, Rezvan; Safdari, Jaber
Abstract : In this study, a new model for prediction of drop size distribution is proposed in the asymmetric rotating disc pilot plant column (ARDC) by the maximum entropy density approximation technique. Abstract : In this study, a new model for prediction of drop size distribution is proposed in the asymmetric rotating disc pilot plant column (ARDC) by the maximum entropy density approximation technique. The liquid extraction systems including toluene–water, n -butyl acetate–water and n -butanol–water were used with this column. An image analysis technique was applied to determine the drop size distribution as a function of operating parameters and physical properties. By applying abrupt changes of the operating parameters, the drop behaviors in the column were investigated. The results show that the agitation speed has a main effect on the drop size distribution in the column. However, the effects of phase flow rates are not significant. The empirical correlations are proposed to describe Lagrange multipliers in the maximum entropy function in terms of operating variables and physical properties of the systems. Except for these findings, an empirical correlation is proposed for estimation of the Sauter mean drop diameter in terms of operating variables, column geometry and physical properties. The proposed correlations are evaluated based on the goodness of fit statistics, namely, χ 2, R 2 and RMSE. The fitting results by the maximum entropy principle method seem to be fairly accurate and reasonable on the basis of the experimental data. These completed sets of data could be used for modeling approaches in the liquid–liquid extraction columns.